2018
DOI: 10.3390/ijerph15102064
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Supplementation and Nordic Walking Training Decreases Serum Homocysteine and Ferritin in Elderly Women

Abstract: The aim of the study was to verify if coupling 12 weeks of vitamin D supplementation and Nordic walking training favoured lowering the homocysteine (Hcy) level. Ninety-four elderly women were divided into three groups: Nordic walking (NW), supplemented (SG) and control (CG). The NW and SG groups received a weekly dose of 28,000 IU of vitamin D3. A blood analysis was performed at baseline, 1h after the first training session and at the end of the experiment. The amino acid profile (methionine and cysteine) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 29 publications
3
10
0
Order By: Relevance
“…In subjects from the NW group, there was a significant decrease in BDNF concentrations after 8 weeks of training. This finding corresponds well with that received after 12 weeks of NW training in elderly women (Walentukiewicz et al, 2018). Unlike the NW group, the upward trend in BDNF concentrations in the NW with RSA group observed in our study is difficult to explain, especially since no reports of this type of training are available.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…In subjects from the NW group, there was a significant decrease in BDNF concentrations after 8 weeks of training. This finding corresponds well with that received after 12 weeks of NW training in elderly women (Walentukiewicz et al, 2018). Unlike the NW group, the upward trend in BDNF concentrations in the NW with RSA group observed in our study is difficult to explain, especially since no reports of this type of training are available.…”
Section: Discussionsupporting
confidence: 85%
“…On the other hand, there is evidence of a post-workout decrease in BDNF concentrations in response to diverse training programs (Correia et al, 2010;Walentukiewicz et al, 2018). In our study concerning post-workout changes in BDNF blood levels in the women examined, the different effects of training loads were demonstrated.…”
Section: Discussionmentioning
confidence: 55%
“…Cholecalciferol was the main form of vitamin D that were supplemented in these studies. The duration of supplementation with vitamin D also varied from 3 h to 6 months [40][41][42][43][44][45][46][47][48][49][50][51][52][53].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Different types of vitamin D were used in these studies, four studies received vitamin D fortified food with cholecalciferol [40,[46][47][48], eight studies received oral vitamin D (cholecalciferol) supplements [42,44,45,[49][50][51][52][53] and in one study subjects were supplemented with ergocalciferol and another one with calcitriol [41,43]. The minimum vitamin D dosage was 20 IU and maximum was 500,000 IU according to these studies ( Table 1).…”
Section: Intervention Characteristicsmentioning
confidence: 99%
“…Moreover, it has been noted that lower levels of 25(OH)D have been associated with increased CRP and Hcy levels as both known as independent risk factors for CVD (30) . A recent study examined the effect of vitamin D supplementation for 12 weeks along with Nordic walking training among elderly women and found that vitamin D along with training helps in reducing the concentrations of CRP and Hcy (40) . The results of the present study agreed with our findings, although their study conducted on elderly women and they combined vitamin D supplementation with walking training.…”
Section: Discussionmentioning
confidence: 99%